Characteristics of Mythological Worlds and their Impact on Human Consciousness - Jamolova Mohigul (Zien Journals, 2022)
This article discusses myth and its types, mythology and its images, and discusses the scholar's scientific basis. The study presents mythological ideas and philosophical views on the impact of worldviews on the universe and the human mind.
Keywords: myth; animistic myths; agricultural culture; perceptions